(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Sesame oil has culinary, medicinal, and industrial uses. It is valued for its distinct aroma, flavour, and health benefits. Due to its high demand and the higher price, the merchants intentionally adulterate low-priced, low-quality edible oil with sesame oil for economic gains without considering consumer health. The present study focused on developing rapid, cost-effective, and straightforward methods for the detection of adulteration of peanut oil with a dual emphasis on facilitating on-site detection as well as enabling laboratory in-house sample analysis. Pure sesame and peanut oil samples were prepared at the laboratory by the expeller method. Using UV-VIS Spectrophotometric analyses, two approaches were established in the first stage of the investigation. For the in-laboratory sample analysis, the absorption spectra of adulterated samples in the UV range were obtained and compared with those of pure sesame and peanut oil. A significant variation in both the highest absorbance level and the corresponding wavelength was observed once the adulteration level reached 50%, enabling detection within the adulteration range of 50% to 100%. To detect adulteration levels between 0% and 50%, the absorbance of the chromogenic complex resulting from the reaction between sesame oil and ethanolic furfural solution was utilized in developing a spectrophotometric analysis. Absorbances recorded at 520 nm for each adulteration exhibited a strong correlation with the sesame oil percentage allowing for detection within the adulteration range spanning 0% to 50%. The latter part of the study focused one stablishing a simple chromogenic test for on-site sample analysis to detect total adulteration level. Hence two chromogenic tests were developed using acidic permanganate and acidic dichromate solutions by availing the higher antioxidant activity of sesame oil.